The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Long, Shuisheng; Li, Zhihao; Dong, Xiaohui; Yan, Xiaobo; Liu, Hao; Tan, Beiping; Zhang, Shuang; Pan, Simiao; Li, Tao; Suo, Xiangxiang; Yang, Yuanzhi (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for haematogenesis and antibody and granulocyte production. However, the effect of oxidised fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) is unknown. In this study, hybrid groupers were fed with oxidised fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidised fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidised fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organisation of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signalling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidised fish oil caused oxidative stress and damaged its structure. Additionally, oxidised fish oil changed the transcription profile of the spleen.